A Jounal for Canada...and the World - Robert B Kalina (Canadian Journal of Gastroenterology)
The gathering and distribution of information has undergone enormous change over the past decade. The electronics revolution has made it possible to collect an ever-increasing amount of data and make it available to an ever-increasing audience at an ever-increasing speed. Publishing peer-review medical journals, of course, is part of this revolution and has undergone as great a change as any member of this group.